Identification of socioenvironmental impacts related to sustainable development goal: a case study in agroecological site (Research, Society and Development, 2021)
Due to the intense environmental degradation caused by conventional agriculture, its techniques, methods and marginalization of small rural producers, it is of great importance a promising alternative for food production. The organic plant shows better nutritional quality, its production avoids or involves workers as pesticides, in addition to providing economic benefits and rural producers. This work aims to present the socio-environmental impacts generated by certified organic production of an agroecological property and benefit the benefits of this activity about the Sustainable Development Goal, recognized by 193 States-Members the United Nations Organization. The survey was carried out using technical visits and intense holistic observation that resulted in Matrices of Identification of Environmental Impacts of Certified Organic Production, which correlates each impact (of positive or negative nature) to the respective SDGs intensified in practice. A correlation was found in 13 two 17 SDGs, concluding a relationship of local production actions that corroborates the global dynamic network, contributing to sustainable development for as well as future generations.